Evaluation of Fungicides for the Control of Rice False Smut (Ustilaginoidea virens) (Bangladesh Rice Journal, 2017)
Outbreak of false smut, caused by the fungus Ustilaginoidea virens has been recorded in recent years in the popular rice variety BRRI dhan49 from various parts of Bangladesh. Registered and/or recommended fungicides are not yet available for chemically controlling the disease. Consequently, uses of unregistered fungicides are common by the farmers for the management of the disease. The present study was, therefore, undertaken to identify effectiveness of any fungicides to control rice false smut disease. Seven synthetic foliar fungicides were evaluated in the naturally induced diseased plots. Each fungicide was applied as spray twice, at panicle initiation and at early flowering stage. Compared to the control (no fungicide application), the fungicide Controller 300 EC reduced the hill infection by 57%, followed by Green 300 EC, Cuprofix 30 Disperss and Diazole 300 EC, each of those suppressed the hill infection by 50%. While Cuprofix 30 Disperss, compared to the control, resulted in the lowest number of infected panicle per hill, it was statistically similar to rest of the fungicides except for Confidence 10 SL. Fungicides and control did not have any significant variation on the number of infected florets per panicle. With respect to per unit (hill infection × number of infected panicle per hill) disease suppression Controller 300 EC was the best. However, none of the fungicides reached the level of the disease suppression, the essential criterion for registration and/or recommendation of a fungicide under Bangladesh conditions. It is concluded that more multi-location and multi-season experiments will be required to reach a decisive conclusion on foliar chemical options for controlling rice false smut disease under Bangladesh conditions.Bangladesh Rice j. 2016, 20(2): 61-66